2017
DOI: 10.3389/fevo.2017.00021
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: A Bird in the House: The Challenge of Being Ecologically Relevant in Captivity

Abstract: In his recent paper Beaulieu (2016) suggested that the conditions in which zebra finches are housed in research laboratories do not represent conditions in the wild, and may be stressful. These findings were based on his consideration of some Australian climate data and the levels of corticosterone reported in a range of published studies. We think there are problems with both Beaulieu's (2016) perspective on climate and day length, and his treatment and interpretation of corticosterone data from the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…These findings are consistent with those found by one of the two similar studies of a passerine (the great tit) breeding in controlled temperature experiments (Schaper and Visser 2013). The other similar study (of zebra finches breeding in cool and moderate temperatures) found no relationship between egg mass and ambient temperature (Salvante et al 2007), although the temperatures in our study are more ecologically relevant to the temperatures in which the species naturally breeds (Griffith et al 2017a). It is also worth noting that the relationship seen in our experimental groups, is relatively weak, and indeed a review across avian species found that temperature likely only explains a small amount (at most 10-15%) of egg-size variation (Christians 2002).…”
Section: Populationsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with those found by one of the two similar studies of a passerine (the great tit) breeding in controlled temperature experiments (Schaper and Visser 2013). The other similar study (of zebra finches breeding in cool and moderate temperatures) found no relationship between egg mass and ambient temperature (Salvante et al 2007), although the temperatures in our study are more ecologically relevant to the temperatures in which the species naturally breeds (Griffith et al 2017a). It is also worth noting that the relationship seen in our experimental groups, is relatively weak, and indeed a review across avian species found that temperature likely only explains a small amount (at most 10-15%) of egg-size variation (Christians 2002).…”
Section: Populationsupporting
confidence: 93%
“…In a number of avian species it has been suggested that egg volume will decline across the laying order when females are nutritionally constrained (Ruuskanen et al ), and it is possible that dietary differences may explain this inter‐population difference. However, there are many other differences between captive populations and the environment in which they are maintained that can drive consistent differences between populations at different institutions (Griffith et al b; see also Supplementary material Appendix 1 Table A4).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, air temperatures follow a clear seasonal pattern, with hot summers and physiologically extreme air temperatures occurring from October through to February (in the Austral spring and summer). The average air temperature in which laboratory populations of Zebra Finches are held (approximately 21 • C) fairly closely reflect the average conditions during breeding in the wild, across an extended breeding period (approximately 19 • C; [39]). However, this value (19 • C) was the long-term average, and Zebra Finches breeding in the early spring will face average, minimal, and maximal conditions that are very different to those experienced by birds breeding a few months later in the summer.…”
Section: Climatic Extremes During Breeding and Developmentmentioning
confidence: 85%
“…It is interesting that they still have a response to the variation in temperature to which we exposed them (18 and 30°C). In the wild, temperature varies to a much greater extent, and eggs are laid in wild nests in periods with a mean daily minimums of around 12°C and mean daily maximum temperatures of 26°C (Griffith et al 2017a). The absolute maximum temperatures in the arid zone are much greater and, during periods of active breeding, ambient conditions regularly exceed 40°C (Griffith et al 2016).…”
Section: Nestmentioning
confidence: 99%
“…In this species, a facultative response to climactic variation is particularly relevant because in the wild, zebra finches breed over an extended period of the year, with mean daily temperatures varying from just 10°C to over 26°C during the breeding period (Griffith et al 2017a), and in the summer, temperatures inside the nest can exceed 50°C (Griffith et al 2016). We have used ecologically relevant average temperatures (18°C and 30°C) to reflect the average conditions in the cooler period in early spring and the hotter period experienced later in the breeding season (based on descriptions of relevant climate in Griffith et al 2016Griffith et al , 2017a. Nests built under the two different temperature treatments were compared and it was hypothesized that if nest building was behaviourally plastic with respect to climate, then a difference in the mass and composition of nests would be observed.…”
Section: Introductionmentioning
confidence: 99%